A randomized controlled trial comparing the Thompson hemiarthroplasty with the Exeter polished tapered stem and Unitrax modular head in the treatment of displaced intracapsular fractures of the hip. - Sims, AL; Parsons, N; Achten, J; Griffin, XL; Costa, ML; Reed, MR (British Editorial Society of Bone and Joint Surgery, 2018)
Aims This study aimed to compare the change in health-related quality of life of patients receiving a traditional cemented monoblock Thompson hemiarthroplasty compared with a modern cemented modular polished-taper stemmed hemiarthroplasty for displaced intracapsular hip fractures. Patients and Methods This was a pragmatic, multicentre, multisurgeon, two-arm, parallel group, randomized standard-of-care controlled trial. It was embedded within the WHiTE Comprehensive Cohort Study. The sample size was 964 patients. The setting was five National Health Service Trauma Hospitals in England. A total of 964 patients over 60 years of age who required hemiarthroplasty of the hip between February 2015 and March 2016 were included. A standardized measure of health outcome, the EuroQol (EQ-5D-5L) questionnaire, was carried out on admission and at four months following the operation. Results Of the 964 patients enrolled, 482 died or were lost to follow-up (50%). No significant differences were noted in EQ-5D between groups, with a mean difference at four months of 0.037 in favour of the Exeter/Unitrax implant (95% confidence interval (CI) 0.014 to 0.087, p = 0.156), rising to 0.045 (95% CI 0.007 to 0.098, p = 0.09) when patients who died were excluded. The minimum clinically important difference for EQ-5D-5L used in this study is 0.08, therefore any benefit between implants is unlikely to be noticeable to the patient. There was no difference in mortality or mobility score. Conclusion Allowing for the high rate of loss to follow-up, the use of the traditional Thompson hemiarthroplasty in the treatment of the displaced intracapsular hip fracture shows no difference in health outcome when compared with a modern cemented hemiarthroplasty.